Polyprodrug Amphiphiles: Hierarchical Assemblies for Shape-Regulated Cellular Internalization, Trafficking, and Drug Delivery - Hu, Xianglong; Hu, Jinming; Tian, Jie; Ge, Zhishen; Zhang, Guoying; Luo, Kaifu; Liu, Shiyong (Journal of the American Chemical Society, 2013)
Solution self-assembly of block copolymers (BCPs) typically generates spheres, rods, and vesicles. The reproducible bottom-up fabrication of stable planar nanostructures remains elusive due to their tendency to bend into closed bilayers. This morphological vacancy renders the study of shape effects on BCP nanocarrier-cell interactions incomplete. Furthermore, the fabrication of single BCP assemblies with built-in drug delivery functions and geometry-optimized performance remains a major challenge. We demonstrate that PEG-b-PCPTM polyprodrug amphiphiles, where PEG is poly(ethylene glycol) and PCPTM is polymerized block of reduction-cleavable camptothecin (CPT) prodrug monomer, with >50 wt % CPT loading content can self-assemble into four types of uniform nanostructures including spheres, large compound vesicles, smooth disks, and unprecedented staggered lamellae with spiked periphery. Staggered lamellae outperform the other three nanostructure types, exhibiting extended blood circulation duration, the fastest cellular uptake, and unique internalization pathways. We also explore shape-modulated CPT release kinetics, nanostructure degradation, and in vitro cytotoxicities. The controlled hierarchical organization of polyprodrug amphiphiles and shape-tunable biological performance opens up new horizons for exploring next-generation BCP-based drug delivery systems with improved efficacy.